Juegos didácticos virtuales como estrategia de aprendizaje de la Química General con los estudiantes de segundo semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Taday Muyolema, Javier Fernando (2024)
Current education requires the integration of digital tools and the practice of pedagogical activities that allow motivation, participation and stimulation in learning. The research problem is based on How does the proposal of virtual didactic games contribute to the learning of general chemistry in second semester students of the Pedagogy of Experimental Sciences, Chemistry and Biology? And the objective of this research was to propose virtual didactic games as a contribution to the learning of General Chemistry. Therefore, an instructive was elaborated that covers the contents of the Units of Chemical Bonds, Structure and Nomenclature of Inorganic Compounds, together with the didactic games developed in a digital way. The methodology used was of quantitative approach with non-experimental design, descriptive scope, bibliographic and field type; and the analysis-synthesis method was used. For data collection, a survey was applied to 33 students through a questionnaire on the Forms platform containing 10 questions with 4 multiple options. With the information collected, it was analyzed that the proposal was accepted by the students, concluding that the application of virtual didactic games in the learning of General Chemistry has a significant impact since it fosters creativity, reasoning, and understanding of knowledge, motivating the desire to learn. Therefore, it is recommended to students to use virtual didactic games as a learning strategy.